Teknik Vokal Tembang Sasak Jati Sware - Hary Murcahyanto; Yuspianal Imtihan; Baiq Rismarini Nursaly; Wawan Syafriawansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to describe the vocal technique of Tembang Jati Sware in the Bebadosan Terune Art Studio, Lenek Village, East Lombok Regency. This research uses descriptive qualitative method. Primary data is the sound of Tembang Jati Sware Pupuh Dang-Dang, while secondary data comes from informants and texts in the form of oral and written. The results showed that when reciting Tembang Jati Sware using chest breathing. Articulation changes occur when the song is read. In Tembang Jati Sware, there are ten sentence breaks, namely on each comma. The body position when the tone is high is upright, the chest is outstretched, and the shoulders are opened, while when the tone is low the body position is normal. The intonation of the song is free, the vibration occurs every last sentence more than 4 beats to 8 beats. The conclusion of this paper is the vocal technique of the Jati Sware Dang-Dang song in Pepaosan which consists of: breathing, articulation, sentence fragments, singing position, intonation, vibration, and improvisation. Keyword: Tembang, Traditional Songs, Vocal Techniques